Microbial Cellulase Production: Current Technologies and Future Prospects - Ishani Borthakur; Rathinasamy Parimala Devi; Subburamu Karthikeyan; Desikan Ramesh; Dhandapani Murugananthi (Journal of Pure and Applied Microbiology)
Enzymes are biocatalysts, that facilitate chemical reactions by lowering their activation energy. Among these, cellulase emerges as a significant enzyme, consisting of a triad of components that work in synergy to degrade cellulosic biomass. Its significance is mostly pronounced in agricultural contexts, where there is an abundance of lignocellulosic biomass making it pivotal for utilization and conversion of biomass. Utilizing the biomass as a substrate for cellulase production offers dual advantages. Firstly, it simplifies the enzymatic synthesis process by the utilization of naturally occurring precursors. Secondly, it contributes to cost reduction by leveraging readily available resources thereby making it economically viable. Microbial cellulases, sourced from diverse microbes found globally, can aid in efficient enzymatic production. Advances in fermentation processes, coupled with the application of biotechnological tools, have significant impacts in production scalability and cost-effectiveness. Optimizing production strategies is crucial to meet the increasing demands of industrial applications while ensuring sustainability. Emphasizing the utilization of biomass substrates and harnessing the potential of emerging biotechnological advancements are key aspects of enzyme production. This review shall aim to provide an in-depth exploration of current cellulase production technologies and future prospects. By elucidating the underlying principles of cellulase catalysis and the intricacies of production methodologies.